Summary Report of the First IAALD Africa Chapter Conference - IAALD (IAALD, 2006)
The First IAALD Africa Conference aimed at creating a platform to share experiences and challenges that would help mobilise and apply agricultural information and knowledge to improve food security, win the fight against hunger...